2018
DOI: 10.1111/ele.13095
|View full text |Cite
|
Sign up to set email alerts
|

Global dung webs: high trophic generalism of dung beetles along the latitudinal diversity gradient

Abstract: At the global scale, species diversity is known to strongly increase towards the equator for most taxa. According to theory, a higher resource specificity of consumers facilitates the coexistence of a larger number of species and has been suggested as an explanation for the latitudinal diversity gradient. However, only few studies support the predicted increase in specialisation or even showed opposite results. Surprisingly, analyses for detritivores are still missing. Therefore, we performed an analysis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 65 publications
4
80
1
3
Order By: Relevance
“…This is a trait-defined cascade phenomenon (Nichols et al 2013a), but our results revealed several positive relationships between the species richness and abundance of dung beetle functional groups and mammal species richness grouped into major trophic guilds. generalist, coprophage and necrophage) were the functional classes least affected by variation in mammal trophic guilds (61% of all comparisons) and this is likely related to high trophic generalism exhibited by dung beetles (Frank et al 2018) which includes coprophagy, necrophagy and saprophagy. Mammals influenced ~78% of the diel activity grouping of dung beetles (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is a trait-defined cascade phenomenon (Nichols et al 2013a), but our results revealed several positive relationships between the species richness and abundance of dung beetle functional groups and mammal species richness grouped into major trophic guilds. generalist, coprophage and necrophage) were the functional classes least affected by variation in mammal trophic guilds (61% of all comparisons) and this is likely related to high trophic generalism exhibited by dung beetles (Frank et al 2018) which includes coprophagy, necrophagy and saprophagy. Mammals influenced ~78% of the diel activity grouping of dung beetles (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Food specialization, particularly on mammalian dung, has clearly played an important role in driving the evolution (Davis et al 2002) and current distribution of dung beetles globally (Frank et al 2018). Food specialization, particularly on mammalian dung, has clearly played an important role in driving the evolution (Davis et al 2002) and current distribution of dung beetles globally (Frank et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bogoni et al, ; Frank, Brückner, Hilpert, Heethoff, & Blüthgen, ). Other studies discussing the relationship between dung beetle diversity, resource availability and climate conclude that both temperature and mammal diversity constitute drivers of dung beetle diversity (Frank et al, ; Muhirwa et al, ). However, these studies were conducted along small climatic scales compared to our large‐scale 3.6 km elevational and 21°C temperature gradient on Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Although dung beetles are commonly assumed to be generalist feeders (Frank et al , ; Hanski & Cambefort, ), species can show preference toward dung of certain mammal species or trophic guilds (Bogoni & Hernández, ; Santos‐Heredia et al , ). However, few studies have specifically tested the attractiveness of dung from mammal species native to the area of study (but see Enari, Koike, & Sakamaki, ; Frank, Hülsmann, Assmann, Schmitt, & Blüthgen, ).…”
mentioning
confidence: 99%
“…Although dung beetles are commonly assumed to be generalist feeders (Frank et al, 2018;Hanski & Cambefort, 1991), species can show preference toward dung of certain mammal species or trophic guilds (Bogoni & Hernández, 2014;Santos-Heredia et al, 2010).…”
mentioning
confidence: 99%